Clinical characteristics of sarcoidosis patients in the United States versus China - Zhou, Ying; Lower, Elyse E.; Feng, Yinping; Du, Shanshan; Li, Huiping; Baughman, Robert P. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Objective: To characterize and compare the disease manifestations between patients with sarcoidosis in China versus the United States using the World Association of Sarcoidosis and Other Granulomatous disease (WASOG) instrument. Methods: Clinical data and disease manifestations were reviewed from sarcoidosis patients from the Shanghai Pulmonary Hospital (China) and University of Cincinnati Medical Center (US). Results: 481 Chinese patients and 522 US patients with sarcoidosis were studied. Extra-pulmonary sarcoidosis was observed more frequently in US patients than Chinese patients. Chinese patients were more likely to develop hypercalcemia or hypercalcuria (23%) compared to US patients (14%) (χ2=18.342, P<0.001), and US White patients were more likely to experience hypercalcemia or hypercalcuria (20%) compared to US Black patients (7.6%) (χ2=16.230, P<0.001). However, Black patients were more likely to have eye involvement (39%) than White patients (26%) (χ2=10.986, P=0.001). Additionally, US patients witnessed more advanced Stage 3 or 4 chest x-ray patterns and lower predicted FVC% and DLCO% compared to Chinese patients (both P<0.001). Conclusion: Compared to US sarcoidosis patients, Chinese patients were older at diagnosis and experienced a lower frequency of extra thoracic involvement, higher incidence of hypercalcemia or hypercalcuria, and less severe lung involvement. These differences were mostly due to the African American patients seen in the US sarcoidosis clinic.